A COMPARATIVE STUDY ON THE USE OF Ã¢â¬ÅKEIGOÃ¢â¬Â BETWEEN FOREIGN AND JAPANESE STUDENTS - Supriatnaningsih, Rina (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2009)
In Japanese there is so called Ã¢â¬ÅkeigoÃ¢â¬Â (honorific/polite expressions). Honorifics (polite expressions) are used to show intimacy with another person and also to distinguish between oneÃ¢â¬â¢s superiors and subordinates. These forms are an integral part of daily life of Japanese people. If we want to adjust to Japanese society, in order able to communicate fluently and apropiately, the use of polite expressions is absolutely required. For this reason, polite expressions are very important in communicating with Japanese people. Therefore foreign studens who are studyng in Japan need to understand polite expressions as much aspossible, event if they are not majoring in Japanese Language and culture. To analize the items above with questionnaires, field data were collected from 50 Japanese students and 50 foreign students. The questionnaires consisted of the following items: (1) the difference in the keigo used by foreign and Japanese student, (2) the difference in usage of first person pronouns, (3) ) the difference when offering something to another person, (4) the difference in a question keigo usage when asking teacher, (5) )the difference in keigo usage when discussing oneÃ¢â¬â¢s teacher with another person, (6) the difference in keigo usage with demonstrative pronouns, (7) students opinions about keigo:differences in levels of difficulty in using keigo, differences in the use of keigo in daily life, difference in the use of keigo in daily family life, differences in the use of iscussing past and present conditions, differences in using keigo correctly and incorrectly, differences in reasons for using keigo, differences in processes of learning keigo. ForeignersÃ¢â¬â¢ opinions clarify that they find difficulties in using keigo as do Japanese students. Eventhough it is difficult, according to the opinions of the Japanese students, the use of keigo expressions is necessary. However, foreign students stated that keigo does not need to be used. Their reasons were: because it is very easy to make mistakes, very difficult to memorize, old language/orthodox, seldom use it, requires complicated consideration at status age, etc. and everyone should have the same status. Considering the opinions mentioned above keigo education for foreign students, especially for Indonesian students, is very much in need. Results of the interviews with Indonesian students illustrate their difficulties. Therefore, in my opinion the following points are most important in teaching Japanese keigo to Indonesian students: (1) the need to inform student a Japanese language has a keigo system and introduce to them the various kinds and forms of keigo, (2) the need to teach keigo grammar (sentence structure), (3) drill, (4) the need to teach appropriate expressions according to context using audio visual materials, (5) conversation practice simulation ÃÂ Key: keigo, foreign and Japanese students.